ANALISIS EFEKTIFITAS PENERIMAAN PAJAK ROKOK DI PROVINSI KALIMANTAN SELATAN - Dori Okta; Akhmad Sayudi (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2020)
The purpose of this study was to determine the target and realization of Cigarette Tax in 2016-2020 in South Kalimantan Province and to determine the analysis of the effectiveness of Cigarette Tax receipts in South Kalimantan Province. Cigarette tax is stipulated in Law Number 28 of 2009 concerning Regional Taxes and Regional Levies. The results of research at the Regional Finance Agency of South Kalimantan Province regarding the effectiveness of Cigarette Tax receipts in 2016 amounted to 100.44%, in 2017 amounted to 97.32%, in 2018 amounted to 87.84%, in 2019 amounted to 72.81%, in 2020 amounted to 81.70%. In 2016-2020, the average level of effectiveness is quite effective, although the realization in 2017-2020 has not yet reached the predetermined target.